Zastosowanie szkoleń opartych na koncepcji konstruktywizmu poznawczego w przygotowaniu do pracy absolwentów wyższych szkół o profilu ekonomicznym - Bartkowiak, Grażyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Human resource development needs to take cognizance of the unique challenges that the workplace of the future is posing to individuals, so that young people can be prepared effectively for the workplace. The objective of the study was to evaluate the training programme based on the principles of cognitive constructivism and focused on preparing people for the workplace of the future. Two groups: an experimental one and a control one were used to evaluate the programme. Each group consisted of nineteen individuals, students of two graduated schools of economics. The training programme contributed to a significant increase of social and economic competences and personal development skills of students, of the experimental, preparing them for the workplace of the future. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 339-348